Manajemen Sumber Daya Manusia pada Generasi Z Pasca Pandemi Covid-19 - Rio Octogi Siregar; Arpi Pratama; Sugiyono Sugiyono (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
The Covid-19 pandemic has significantly transformed the landscape of the working world, coinciding with the entry of Generation Z into the workforce. This study examines the paradigm shifts in human resource management (HRM) necessary to accommodate the unique characteristics of Generation Z in a post-pandemic context. Through comprehensive literature analysis and case studies, this research identifies key strategies in HRM, including technology adoption, work flexibility, continuous development, and a focus on holistic well-being. The findings indicate that organizations need to adopt more personalized, digital, and purpose-driven approaches to attract, retain, and develop Generation Z talent. This study provides valuable insights for HR practitioners and organizational leaders in designing effective HRM strategies in the post-pandemic era.